Job satisfaction among licensed librarian along Herzberg's Hygiene-Motivation theory in the Philippine setting - Wee, Ma Mercedes L. (Institute of Library Science, University of the Philippines Diliman, 2000)
The study focused on job satisfaction of licensed librarians. It sought to answer the following questions: What determines the level of satisfaction of licensed librarians along Herzberg's-Motivation Theory What are the educational programs and alternative means to enhance the job satisfaction of these librarians Is Herzberg's Hygiene-Motivation Theory applicable to librarians professional Data were collected by means of questionnaires and interviews. The sample included 204 licensed librarians from the different types of libraries namely: special, public, school and academic and research libraries.